High dynamic range photography without a tripod: A linear formulation for image fusion. Issue 2 (27th May 2014) - Barazzetti, Luigi
Abstract : Purpose: – The purpose of this paper is to present a new multi-image registration methodology that is able to align a set of hand-held bracketed shots. Design/methodology/approach: – The procedure is a two-step algorithm where corresponding multi-image points are automatically extracted from the bracketed image sequence and a least squares adjustment recovers transformation parameters. Findings: – The images can be processed with high dynamic range algorithms to combine multiple low dynamic range pictures into a single mosaic with a superior radiometric quality. Originality/value: – Simulated and real examples are illustrated to prove the effectiveness of the developed affine-based procedure.